CONSUMERS’ INTENTION TO SWITCH FROM PRINTED BOOK TO E-BOOK IN SURABAYA - Liander, Kevin; Margaretha, Silvia; Anandya, Dudi (Journal of Management and Business, 2016)
The objective of this research is to know the factors that drives consumer to changes their reading behaviour from printed books to e-book using the switching behaviour theory. There are 5 variables that were used in this research, and those variables are new product attributes, social influences, price, switching cost, and intention to switch. This research finds that compatibility, convenience and switching cost have a significant impact on intention to switch, as well as the moderating effect of low switching cost between the relation of compatibility and social influences with intention to switch.